Trusted Node-Based Algorithm to Secure Home Agent NATed IPv4 Network from IPv6 Routing Header Attacks - Mohamed Shenify (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
Providing a secure mobile communication in mixed IPv4/IPv6 networks is a challenging task. One of the most critical vulnerabilities associated with the IPv6 protocol is the routing header that potentially may be exploited by attackers to bypass the security. This paper discusses an algorithm to secure home agent network from the routing header vulnerability, where the home agent network uses IPv4 Network Address Translation (NAT) router. The algorithm also takes into account multi-hops destination in the routing header. Verification was done through implementation of the algorithm at the Home Agent modul in a testbed network. The experimental results show that the proposed algorithm provides secure communication between Correspondent nodes and Mobile Nodes that moved into the NATed network without causing a significance filtering delay.